2001
DOI: 10.1046/j.1469-8137.2001.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope discrimination by Sorghum bicolor under CO2 enrichment and drought

Abstract: Summary• Sorghum bicolor was exposed to free-air CO 2 enrichment (FACE) and drought at the Maricopa Agricultural Center, AZ, USA, in summer 1998. We predicted that bundle sheath leakiness ( Φ ) would be insensitive to FACE under well-irrigated (wet) conditions, but would be lower in FACE compared with control-CO 2 treatments when irrigation was withheld (dry).• Leaf and air δ 13 C values and leaf p i / p a from gas exchange were measured to estimate carbon isotope discrimination ( ∆ ) and Φ . Midday leaf water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 29 publications
7
70
2
1
Order By: Relevance
“…Growth conditions (e.g. elevated CO 2 and water stress) have also been reported to influence the balance of the C 4 and C 3 cycles, leading to an altered isotopic composition of dry matter (Watling et al, 2000;Williams et al, 2001), although the influence on CA was not addressed in these studies.…”
mentioning
confidence: 63%
“…Growth conditions (e.g. elevated CO 2 and water stress) have also been reported to influence the balance of the C 4 and C 3 cycles, leading to an altered isotopic composition of dry matter (Watling et al, 2000;Williams et al, 2001), although the influence on CA was not addressed in these studies.…”
mentioning
confidence: 63%
“…Among them the variations of CO 2 concentration in the environment exerts the strongest effect. High CO 2 concentrations results in 12 C enrichment of biomass in the in vitro experiments [11,20,23]. Similarly pH manifests itself in aquatic environment.…”
Section: Cmentioning
confidence: 99%
“…Later the role of carbon isotope effect of photorespiration was recognized as important [22,28] and some researchers have indicated the role of oxygen concentration on photorespiratory function of Rubisco [23,29]. It was shown that low O 2 content caused the observed enrichment of organic matter 12 C [30].…”
Section: Cmentioning
confidence: 99%
“…C is at least in part associated with p i p a 21 (Madhavan et al, 1991;Henderson et al, 1992Henderson et al, , 1998Williams et al, 2001). As this association is not as strong as in C 3 species, the involvement of additional processes is very likely.…”
mentioning
confidence: 96%